Multi-Responsive Silk Fibroin-Based Nanoparticles for Drug Delivery - Ma, Ya; Canup, Brandon S. B.; Tong, Xiaoling; Dai, Fangyin; Xiao, Bo (Frontiers in Chemistry, 2020)
Silk fibroin has the merits of biocompatibility, biodegradability, ease of processing, and feasibility of modification, which present it as a promising drug delivery material. This review focuses on the structures of silk fibroin, the controlled transformation of secondary structures, and the formation mechanism of silk fibroin-based nanoparticles (SFNPs). We also discuss the intrinsic multi-responsibility, surface functionalization, and transgenic modification of SFNPs for drug delivery.